2005
DOI: 10.1159/000084283
|View full text |Cite
|
Sign up to set email alerts
|

Martial Arts Injuries

Abstract: Preventive measures should focus on education of coaches, referees, athletes, and tournament directors. Although descriptive research should continue, analytical studies are urgently needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
73
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(81 citation statements)
references
References 18 publications
3
73
0
4
Order By: Relevance
“…The women presented contusions rather, without statistically significant difference (P = 0.067) and the men of the fractures significantly (P = 0.041). This tendency was found in the literature with, within the framework of injuries of sport in general, of the more significant of distortions and contusions, and less frequencies of fracture at the ladies (Pieter, 2005). In our study, the distribution of the injuries, according to parts' of the body injured, were comparable with that of concerning the injuries of the judo.…”
Section: Discussionsupporting
confidence: 85%
“…The women presented contusions rather, without statistically significant difference (P = 0.067) and the men of the fractures significantly (P = 0.041). This tendency was found in the literature with, within the framework of injuries of sport in general, of the more significant of distortions and contusions, and less frequencies of fracture at the ladies (Pieter, 2005). In our study, the distribution of the injuries, according to parts' of the body injured, were comparable with that of concerning the injuries of the judo.…”
Section: Discussionsupporting
confidence: 85%
“…There are also other researchers who reported negative outcomes of the martial arts. Such negative outcomes could be seen in terms of injury related problems (Kazemi, et al, 2009;Landa, 2004;Pieter, 2005;Zetaruk et al, 2005), psychosocial problems (Endresen & Olweus, 2005;Lotfian, Ziaee, Amini, & Mansournia, 2011), health related problems (Wargo, Spirrison, Thorne, & Henley, 2007), and unhealthy weight management of athletes (Kazemi, Alima, & Ciantis, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, injuries are more common and could include: brain injuries, broken bones, tears of the knees, sprains of the shoulders and ankles, cuts and bruises, bloody noses, and assorted infections. Pieter (2005) studied the literature regarding injuries of children in the martial arts. It is found that in TKD more injured parts of the body are the lower extremities and sprains.…”
mentioning
confidence: 99%
“…The negative effect of the martial arts found by different studies can be categorized as psychosocial problems (see, Endresen & Olweus, 2005;Lotfian, Ziaee, Amini, & Mansournia, 2011), health related problems (see, Wargo, Spirrison, Thorne, & Henley, 2007), injury related problems (see, Kazemi, et al, 2009;Landa, 2004;Pieter, 2005;Zetaruk, et al, 2004), and unhealthy weight management of athletes (see, Kazemi, Alima, & Ciantis, 2011). There are also researches that showed even participating in different types of the same martial arts (i.e., modern and traditional) can result in different outcomes.…”
Section: Introductionmentioning
confidence: 99%